2004
DOI: 10.1074/jbc.m405194200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced Matrix Metalloproteinase 9 Gene Expression Is Differentially Regulated by ERK1/2 and p38 MAPK in Oral Keratinocytes and Oral Squamous Cell Carcinoma

Abstract: Matrix metalloproteinases (MMPs) play an important role in the invasive behavior of a number of cancers including oral squamous cell cancer (OSCC), and increased expression of MMP-9 is correlated with invasive and metastatic OSCC. Because calcium is an important regulator of keratinocyte function, the effect of modulating extracellular calcium on MMP-9 expression in OSCC cell lines was evaluated. Increasing extracellular calcium induced a dose-dependent increase in MMP-9 expression in immortalized normal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Similarly, the ability of TGFβ to induce MMP-9 expression in prostate cancer cells is acquired during cellular transformation (Sehgal et al, 1996;Sehgal and Thompson, 1999). In addition, changes in calcium-mediated regulation of MMP-9 expression occur during malignant transformation of oral keratinocytes (Mukhopadhyay et al, 2004). Thus, it is clear that certain signaling pathways that regulate MMP-9 expression are activated or altered during cellular immortalization or malignant progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the ability of TGFβ to induce MMP-9 expression in prostate cancer cells is acquired during cellular transformation (Sehgal et al, 1996;Sehgal and Thompson, 1999). In addition, changes in calcium-mediated regulation of MMP-9 expression occur during malignant transformation of oral keratinocytes (Mukhopadhyay et al, 2004). Thus, it is clear that certain signaling pathways that regulate MMP-9 expression are activated or altered during cellular immortalization or malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…mitogen-activated protein kinases (MAPKs) p38 and/or extracellular signal-regulated kinase (ERK) (Johansson et al, 2000;McCawley et al, 1998;Mukhopadhyay et al, 2004;Westermarck and Kahari, 1999;Zeigler et al, 1999). In addition, several studies have demonstrated the importance of cell adhesion in regulating the expression of MMP-9 or other MMPs in immortalized epithelial cells or carcinoma-derived cells (DiPersio et al, 2000;Lochter et al, 1999;Morini et al, 2000;Thomas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SCC9 and SCC25 cells were obtained from American Type Culture Collection (ATCC) Rheinwald and Beckett, 1981), whereas UMSCC1 cells were generously provided by Ernst Lengyel (University of Chicago, IL) (Juarez et al, 1993;Lengyel et al, 1995). SCC68 cells and tertimmortalized normal oral keratinocytes (OKF4 and OKF6 cells) were kindly provided by James G. Rheinwald (Brigham and Women's Hospital, Harvard Institutes of Medicine, Boston, MA) (Dickson et al, 2000;Mukhopadhyay et al, 2004). SCC9, SCC25 and UMSCC1 cells were routinely maintained in DMEM and Ham's F-12 medium (1:1) supplemented with 10% fetal calf serum and 100 units/ml penicillin and 100 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…[24][25][26][27] Twenty microliters of each reaction mixture were analyzed by 1.0% agarose gels in the presence of 0.5 lg/ml ethidium bromide, and DNA was visualized under UV light. Results from real-time PCR were presented as threshold cycles normalized to that of the GAPDH gene according to the method of Overbergh et al 28 It reversibly represented the number of cDNA copies of an individual gene.…”
Section: Rna Isolation and Rt-pcr Analysismentioning
confidence: 99%